VIONE: An Innovative Electronic Health Record Medication Optimization Methodology - Saraswathy Battar (Internal Medicine, 2022)
VIONE methodology is an award winning, USA based patient safety project that transformed our national landscape with High Reliability Organization (HRO) concepts. VIONE’s clinical, academic, research, leadership, modern technology tools achieve sustainable reductions and optimization of Potentially Inappropriate Medications (PIM) and adverse outcomes such as hospitalizations, falls, death, clinical waste, etc. VIONE exemplifies successful project initiation, refinement, incremental expansion to regional, national, and international therapeutic and global alliances.